Cronkhite-Canada Syndrome: A rare Case Report from Nepal - Pokharel, Nitesh R.; Shrestha, Prajwol; Sharma, Vivek; Pandey, Sumit (Journal of Nepal Health Research Council, 2021)
Cronkhite-Canada syndrome first described in 1955, is a rare clinical syndrome of unknown etiology. Since then, more than 500 cases have been reported worldwide in the literature. The disease is characterized by diffuse gastrointestinal polyposis, dystrophic changes of the fingernails, cutaneous hyperpigmentation, alopecia, diarrhea, weight loss, and abdominal pain. A 84-year-old woman was admitted in our hospital with severe dehydration following diarrhea and epigastric discomforts. She also had dystrophic change of fingernails, and pigmentation of the palm and alopecia, all of which began several months ago. Endoscopy showed numerous, dense, tiny red polyps throughout the stomach, and duodenum. Her clinical manifestations and endoscopy were consistent with Cronkhite-Canada syndrome. We prescribed oral corticosteroids, which dramatically improved her condition. We here report rare case of Cronkhite-Canada syndrome who presented to our hospital. Keywords: Cronkhite-canada syndrome; gastrointestinal polyposis; onychodystrophy nail